Gondwanan Palynomorphs From The Paleogene Sediments Of East Java The Evidence Of Earlier Arrival - Eko Budi Lelono (Scientific Contributions Oil and Gas, 2007)
The palynological investigation of the Paleogene sediments is based on cutting samples collected from the exploration wells which are drilled in East Java area. The occurrence of pollen Meyeripollis naharkotensis and spore Cicatricosisporites dorogensis in the upper well sections suggests the pollen zone of Meyeripollis naharkotensis which is equivalent to Oligocene age. Meanwhile, the occurrence of pollen Proxapertites operculatus and spore Cicatricosisporites eocenicus below Meyeripollis naharkotensis zone indicates the appearance of Proxapertites operculatus zone within the lower sections which is equivalent to Eocene. In addition, foraminiferal and nannoplankton analyses confirm the Oligocene-Eocene age by identifying the occurrence of letter stage of Te4-Tb and nanno zone of NP20-P25. The appearance of the Gondwanan/Australian elements including Dacrydium and Casuarina with common and regular occurrences throughout the studied sections are controversial as these pollen were firstly recorded in the younger sediments (Early Miocene) of other areas such as Northwest Java sea, South Sumatra and Natuna sea following the collision of the Australian plate and the Sundaland in the latest Oligocene. Furthermore, the absence of these palynomorphs within the Paleogene sediments of Central Java and South Sulawesi strengthens the above assumption. Therefore, in regard to East Java, the appearance of Dacrydium and Casuarina may indicate earlier arrival of the Gondwanan/ Australian fragment in this area compared to that in other areas of Indonesia.